Antioxidant, Immunomodulating, and Microbial-Modulating Activities of the Sustainable and Ecofriendly Spirulina. (15th January 2017) - Finamore, Alberto; Palmery, Maura; Bensehaila, Sarra; Peluso, Ilaria
Abstract : The highly nutritional and ecofriendly Spirulina ( Arthrospira platensis ) has hypolipidemic, hypoglycemic, and antihypertensive properties. Spirulina contains functional compounds, such as phenolics, phycocyanins, and polysaccharides, with antioxidant, anti-inflammatory, and immunostimulating effects. Studies conducted on Spirulina suggest that it is safe in healthy subjects, but attitude to eating probably affects the acceptability of Spirulina containing foods. Although the antioxidant effect of Spirulina is confirmed by the intervention studies, the concerted modulation of antioxidant and inflammatory responses, suggested by in vitro and animal studies, requires more confirmation in humans. Spirulina supplements seem to affect more effectively the innate immunity, promoting the activity of natural killer cells. The effects on cytokines and on lymphocytes' proliferation depend on age, gender, and body weight differences. In this context, ageing and obesity are both associated with chronic low grade inflammation, immune impairment, and intestinal dysbiosis. Microbial-modulating activities have been reported in vitro, suggesting that the association of Spirulina and probiotics could represent a new strategy to improve the growth of beneficial intestinal microbiota. Although Spirulina might represent a functional food with potential beneficial effects on human health, the human interventions used only supplements. Therefore, the effect of food containing Spirulina should be evaluated in the future.